2006
DOI: 10.1373/clinchem.2006.067512
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Tissue HER2 Status Using Serum HER2 Levels in Patients with Metastatic Breast Cancer

Abstract: Background: Immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) are reliable ways to identify amplification of the HER-2/neu (HER2, symbol ERBB2) gene, but each technique requires a high-quality tissue sample, which may not be available. We investigated whether serum concentrations of the HER2 extracellular domain (ECD) can be used as an alternative to tissue HER2 status in metastatic breast cancer, and we defined an optimal decision level of serum HER2 for prediction of tissue HER2 status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 21 publications
1
32
0
2
Order By: Relevance
“…First, using the cutoff value, 15 ng/ml, which is most widely used in breast cancer (7,9,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), the evaluable 100 patients were stratified into serum HER2-positive (≥15 ng/ml) or -negative (<15 ng/ml) groups, as well as. Sensitivity and specificity were defined as the proportion of the true-positive (TP)/true-negative (TN) patients among tissue HER2-positive/negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, using the cutoff value, 15 ng/ml, which is most widely used in breast cancer (7,9,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), the evaluable 100 patients were stratified into serum HER2-positive (≥15 ng/ml) or -negative (<15 ng/ml) groups, as well as. Sensitivity and specificity were defined as the proportion of the true-positive (TP)/true-negative (TN) patients among tissue HER2-positive/negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum HER-ECD levels represent a promising surrogate marker, various technical variables limit its wide application. The most important issues that have to be clarified are the optimal serum HER-ECD concentration threshold for differentiation between positive and negative HER status and the relatively low sensitivity and specificity of the method currently applied (42). Recently, a pooled analysis of seven clinical trials of first-line trastuzumab therapy (with or without chemotherapy) with serial measurements of serum HER-ECD indicated that patients with <20% decrease in serum HER-ECD levels have lower clinical benefit (31).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to use this serum-based test as the sole classifier of HER-2 status for newly diagnosed cases have not been widely accepted, although fairly good correlation exists between serum HER-2 ECD levels and the results of IHC and FISH assessments on primary tumor tissues [228]. It has been recommended that a 37 g/l serum HER-2 ECD cutoff be used, which can achieve 95% specificity but low sensitivity for HER-2-positive status determined on primary tumors [229]. Studies of breast cancer prognosis based on the serum ECD test have been conflicting, with some finding significant correlation [116] and others finding weak or no correlation [230].…”
Section: Tissue and Serum Enzyme-linked Immunosorbentmentioning
confidence: 99%